Adipokines Identify Crucial Biomarkers for Hypertension in Iraq: Adipokin Mengidentifikasi Biomarker Penting untuk Hipertensi di Irak - Zainab F. Salbookhh; Usama H. Ramadhan; Gibran K. Hassan (Academia Open, 2024)
Adipokines, which are generated by adipose tissue, are biologically active compounds that function similarly to traditional hormones. These proteins are involved in cellular signaling and control or modify several biological processes in target organs such as the brain, liver, muscles, heart, blood vessels, pancreas, and immune system. Adipokines can be incorporated into new diagnostic approaches as biological indicators of different metabolic, inflammatory, and cardiovascular conditions. The study was conducted at Al-Basrah Teaching Hospital on hypertensive patients between December 2022 and March 2023. This study included a sample of fifty-three patients with hypertension, whose ages ranged from 30 to 60 years. The features of these patients were compared to the same variables in a group of fifty-three healthy volunteers aged 30 to 40 years. This study aimed to identify the most significant alterations in serum apelin, spexin, and serum electrolyte levels (sodium, potassium, calcium, magnesium, and chloride) in patients solely diagnosed with hypertension. The analysis involved a statistical examination of the variables. The hypertension group had lower apelin and higher spexin levels than the control group. Additionally, each group had normal electrolyte levels (sodium, potassium, calcium, magnesium, chloride). The control group had somewhat higher potassium, calcium, and chloride levels than the hypertension group. The concentration of apelin does not influence sodium, calcium, magnesium, or chloride. Negative potassium correlation for apelin. However, spexin concentration does not impact sodium, potassium, calcium, or magnesium. Spexin concentrations are negatively correlated with apelin and chloride concentrations. Highlight: Adipokines Role: Adipokines are key in cellular signaling affecting multiple organs. Study Findings: Hypertensive patients showed lower apelin and higher spexin levels. Serum Electrolyte Levels: normal in both groups, with minor differences in potassium, calcium, and chloride. Keywoard: Adipokines, Hypertension, Apelin, Spexin, Electrolytes